EVALUATING THE DEPENDENCE OF DIMENSIONAL STABILISATION OF CHEMICALLY MODIFIED CELTIS MILDBRAEDII (ESA FUFUO) - Marfo, E. D.; Darkwa, N. A. (UDS International Journal of Development, 2019)
Wood absorbs moisture from the surrounding environment and releases moisture according to the temperature and the relative humidity of the surrounding environment leading to dimensional changes. Changes in dimensions can be reduced by chemical modification. The reduced dimensional changes of chemically modified wood depends on either the degree of blocking the hydroxyl groups of the wood polymers in the cell walls and/or bulking the cell wall to reduce the amount of water that can be absorbed into the wood cell wall. However,there is a conflicting result in literature concerning the dependence of absorption of water molecules into the cell wall. In this study, Celtis mildbraedii (esa fufuo), a tropical hardwood species was chemically modified and the dependence of dimensional stabilisation of the chemically modified esa fufuo has been evaluated. The dimensional stability of the modified samples was found to be dependent on bulking at a weight percentage gain below 20%. Keywords: Bulking, Hydroxyl Substitution, Weight Percentage Gain, Hydrogen Bonding, Cell Wall Polymers